Nanosuspension: A Nano-Heterogeneous Carrier for Drug Delivery System - Malakar, J (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACT The basic challenge in pharmaceutical research is to achieve maximum bioavailability for desired therapeutic efficacy but poorly soluble drug always suffers from its erratic absorption as well as bioavailability. Nanosuspension technology can be used resolve the problems of low aqueous solubility and bioavailability. Nanosuspension can be applicable to all less aqueous soluble drugs and it acts tremendously to modify solubility as it belong to a few nanometer size solute particles. The various technologies that have come to prepare nanosuspension are precipitation, milling, high pressure homogenization, emulsion and microemulsion method, dry co-grinding, supercritical fluid method. Nanosuspensions can be delivered by oral, parenteral, pulmonary and ocular routes. Nanosuspensions can also be used for targeted drug delivery when incorporated in the ocular inserts and mucoadhesive hydrogels.